Knowledge, atiitude and practice (KAP) and associated factors for leptospirosis among town service workers in Kota Bharu, Kelantan - Shafei, Mohd Nazri (Pusat Pengajian Sains Peruabatan, Universiti Sains Malaysia, 2009)
Introduction: Leptospirosis is presumed to be the most widespread re-emerging zoonotic disease in the world. This study was designed to determine the seroprevalence, explore the knowledge, attitude, and practice (KAP) and to determine the associated factors for seropositive leptospirosis among town service workers in Kota Bharu Municipal Council (MPKB), Kelantan. Methods: A cross sectional study was conducted in May 2008 among 296 town service workers in Kota Bharu Municipal Council. Workers were interviewed using a validated questionnaire and venous blood was taken from each subject at their workplace for microscopic agglutination test (MAT). Results: All respondents were Malay males with the mean age of 42.1 (SD 8.38) years old. The overall seroprevalence of leptospirosis was 24.7% In the KAP assessment, majority of workers had poor knowledge (87.2%) and unsatisfactory practice score (64.5%). The significant factors associated with seropositive leptospirosis were those who live :'S 200 meters from river, present of rat in their house, and involved in gardening activity. Workers who practiced wearing boots while working, and washing hands with soaps after works had protective effect towards leptospirosis. Conclusion: High seropositivity rates of leptospirosis indicate that town service workers are occupational risk group for leptospiral infection. Workers' knowledge and practice was inadequate to protect them from leptospirosis infection. There is close relationship between seropositive leptospirosis with occupational and environmental factors as well as recreational activities. ..